2013
DOI: 10.1002/oby.20103
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptor delta protects against obesity‐related glomerulopathy through the P38 MAPK pathway

Abstract: Objective: Obesity is a prominent component of metabolic syndrome and a major risk factor for renal disease. The aim of this study was to explore the effect of cross-talk between peroxisome proliferatoractivated receptor (PPAR)d and p38 mitogen-activated protein kinase (p38 MAPK) on obesity-related glomerulopathy. Design and Methods: Male Wistar rats were randomly assigned to standard laboratory chow or a highfat diet for 32 weeks. Glomerular mesangial cells HBZY-1 and mature differentiation 3T3-L1 cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…anti-inflammatory role of PPARδ in CS-related airway inflammation. It has been found that treatment with a synthetic PPARδ agonist inhibited activation of p38 MAP kinases in inflammatory circumstance, 19,28,32 which suggested a tight link between PPARδ and p38 MAPK. The MAPK family includes three members: p38, ERK and c-Jun N-terminal kinase (JNK).…”
Section: Discussionmentioning
confidence: 99%
“…anti-inflammatory role of PPARδ in CS-related airway inflammation. It has been found that treatment with a synthetic PPARδ agonist inhibited activation of p38 MAP kinases in inflammatory circumstance, 19,28,32 which suggested a tight link between PPARδ and p38 MAPK. The MAPK family includes three members: p38, ERK and c-Jun N-terminal kinase (JNK).…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK pathway has also been shown to play an important role in obesity and its activation has been implicated in obesity-related complications such as ORG (Yan et al, 2013). JNK, p38, and ERK, the three main subfamilies of MAPKs, have all been reported to be activated in response to inflammatory and stress-inducing stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, the PPAR-g agonist rosiglitazone has been shown to downregulate gonadotropin-releasing hormone-mediated phosphorylation of p38 MAPKs in LbT2 cells (Sakaida et al, 2004). In addition, Yan et al (2013) reported that obesity-related glomerulopathy may be caused in part by suppressed PPAR-g expression and increased p38 MAPK activation. Accordingly, we hypothesized that HSYA ameliorated hepatic fibrosis through regulation of the PPAR-g/p38 MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%